Copernicus Sentinels missions and crowdsourcing as game changers for geospatial information in agriculture - Flavio Lupia; Vyron Antoniou (GEOmedia, 2018)
A big leap in the agricultural sector is expected thanks to the operational deployment of Copernicus data and services, the new Earth Observation program of the European Commission. The huge quantity of data delivered freely along with the good level of resolution (spatial, temporal and spectral) will open up new opportunities for achieving the well-known sustainability of agriculture. At the same time, the new trends of crowdsourcing and citizen science are delivering a great deal of geographical data collected by ordinary users with a bottom-up process. The two type of data and their integration will be the base for the future application in the agricultural sector, albeit management of big geospatial dataset and quality of user generated data are issues to be addressed.